The teacher will be very surprised to see your correct solution 😉

You have entered
[src]

78 x 11 -- - -- = -- 97 97 97

$$- \frac{x}{97} + \frac{78}{97} = \frac{11}{97}$$

Detail solution

Given the linear equation:

Move free summands (without x)

from left part to right part, we given:

$$- \frac{x}{97} = - \frac{67}{97}$$

Divide both parts of the equation by -1/97

We get the answer: x = 67

78/97-x/97 = 11/97

Move free summands (without x)

from left part to right part, we given:

$$- \frac{x}{97} = - \frac{67}{97}$$

Divide both parts of the equation by -1/97

x = -67/97 / (-1/97)

We get the answer: x = 67

Sum and product of roots
[src]

sum

67

$$\left(67\right)$$

=

67

$$67$$

product

67

$$\left(67\right)$$

=

67

$$67$$

The graph